A Fluorescent Aptasensor Based on Assembled G-Quadruplex and Thioflavin T for the Detection of Biomarker VEGF165 - Zheng, Xin; Gao, Shunxiang; Wu, Jihong; Hu, Xiaobo (Frontiers in Bioengineering and Biotechnology, 2021)
VEGF165, a regulator of angiogenesis, has been widely used as a serum biomarker for a number of human diseases, including cancer, rheumatoid arthritis, bronchial asthma, and diabetic eye disease. The rapid, accurate, and convenient detection of VEGF165 is a crucial step in effective healthcare monitoring, disease diagnosis, and prognosis assessment. In this study, a fluorescent aptasensor based on an assembled G-quadruplex and the signal molecule ThT was developed for VEGF165 detection. First, G-rich DNA fragments were assembled at both ends of the anti-VEGF165 aptamer, and the B-DNA form was converted into a G-quadruplex structure aptamer (G4-Apt). Then, ThT was introduced, and the G-quadruplex significantly enhanced the fluorescence intensity of the bound ThT. When VEGF165 was present, the higher affinity of the aptamer to the target protein allowed the G4-Apt/VEGF165 complex to form and release ThT, which emitted only weak fluorescence in the free state. Therefore, the aptasensor exhibited a good linear detection window from 1.56 to 25 nM VEGF165, with a limit of detection of 0.138 nM. In addition, the aptasensor was applied to detect VEGF165 in clinical serum samples, showing good accuracy, reproducibility, and stability. These results indicate that our developed fluorescent aptasensor can potentially be a reliable, convenient, and cost-effective approach for the sensitive, specific, and rapid detection of the VEGF165 biomarker.